2020
DOI: 10.1161/circimaging.120.011491
|View full text |Cite
|
Sign up to set email alerts
|

Ejection Fraction by Echocardiography for a Selective Use of Magnetic Resonance After Infarction

Abstract: Background Cardiac magnetic resonance (CMR) permits robust risk stratification of discharged ST-segment–elevation myocardial infarction patients, but its indiscriminate use in all cases is not feasible. We evaluated the utility of left ventricular ejection fraction (LVEF) by echocardiography for a selective use of CMR after ST-segment–elevation myocardial infarction. Methods Echocardiography and CMR were performed in 1119 patients discharged for ST-segm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 19 publications
1
29
0
1
Order By: Relevance
“…Leading on from previous research to determine which patients could benefit most from CMR for prognostic purposes, e.g. those with echocardiography-LVEF<50% [7], the present study focuses on simple risk prediction in patients who undergo CMR. This technique is recommended when echocardiography is suboptimal or inconclusive, and brings the added benefit of additional assessment of residual ischemia and myocardial viability [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leading on from previous research to determine which patients could benefit most from CMR for prognostic purposes, e.g. those with echocardiography-LVEF<50% [7], the present study focuses on simple risk prediction in patients who undergo CMR. This technique is recommended when echocardiography is suboptimal or inconclusive, and brings the added benefit of additional assessment of residual ischemia and myocardial viability [4].…”
Section: Discussionmentioning
confidence: 99%
“…Use of cardiac magnetic resonance (CMR) in this setting has increased exponentially this century. CMR performed early after the acute event permits comprehensive evaluation of the structural consequences of myocardial infarction and can improve risk prediction by means of accurate LVEF, microvascular obstruction (MVO) and infarct size (IS) measurement [5][6][7]. Exploring the prognostic value of novel predictive scores including CMR parameters is therefore an essential undertaking.…”
Section: Introductionmentioning
confidence: 99%
“…3,7 We recently showed that significant crossovers can occur between LVEF categories when pre- discharge values from echocardiography and MRI are compared. 12 Risk reconsideration in chronic phase has shown an impact on decision-making. Patients with less closely monitored LVEF are less likely to be treated with specific evidence-based medications and implantable cardioverter-defibrillators.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, based on the high MACE rate detected in patients with LVEF < 40% (vs. those with ≥40%) both at 1 week and after follow‐up MRI in this registry and previous analysis by our group, 12 additional analyses were performed using this cut‐off value to study the prognostic impact of LVEF dynamics (i.e., LVEF change from initial to follow up). Consequently, patients were classified into Group 1—sustained LVEF < 40% (“r‐ to r‐LVEF”), Group 2—worsened LVEF (“p‐ or mr‐ to r‐LVEF”), Group 3—improved LVEF (“r‐ to mr‐ or p‐LVEF”), and Group 4—sustained LVEF ≥ 40% (“mr‐ or p‐ to mr‐ or p‐LVEF”).…”
Section: Methodsmentioning
confidence: 99%
“…A recent study suggested use of CMR for further risk stratification on STEMI patients with lower LVEF on echocardiography. 36 Thus, with a multiple‐sequence design in our CMR protocol for this trial, we proposed that PERI‐STEMI could better demonstrate the advanced functional benefits ARNI could bring, as well as pave understanding of its cardiovascular mechanism.…”
Section: Discussionmentioning
confidence: 99%